Forward Surgical Team Procedural Burden and Non-operative Interventions by the U.S. Military Trauma System in Afghanistan, 2008–2014. Issue 5 (20th December 2019) - Staudt, Amanda M; Suresh, Mithun R; Gurney, Jennifer M; Trevino, Jennifer D; Valdez-Delgado, Krystal K; VanFosson, Christopher A; Butler, Frank K; Mann-Salinas, Elizabeth A; Kotwal, Russ S
Abstract: Introduction: No published study has reported non-surgical interventions performed by forward surgical teams, and there are no current surgical benchmarks for forward surgical teams. The objective of the study was to describe operative procedures and non-operative interventions received by battlefield casualties and determine the operative procedural burden on the trauma system. Methods: This was a retrospective analysis of data from the Joint Trauma System Forward Surgical Team Database using battle and non-battle injured casualties treated in Afghanistan from 2008–2014. Overall procedure frequency, mortality outcome, and survivor morbidity outcome were calculated using operating room procedure codes grouped by the Healthcare Cost and Utilization Project classification. Cumulative attributable burden of procedures was calculated by frequency, mortality, and morbidity. Morbidity and mortality burden were used to rank procedures. Results: The study population was comprised of 10, 992 casualties, primarily male (97.8%), with a median age interquartile range of 25.0 (22.0–30.0). Affiliations were non-U.S. military (40.0%), U.S. military (35.1%), and others (25.0%). Injuries were penetrating (65.2%), blunt (32.8), and burns (2.0%). Casualties included 4.4% who died and 14.9% who lived but had notable morbidity findings. After ranking by contribution to trauma system morbidity and mortality burden, the top 10 of 32 procedure groups accounted for 74.4% of operative care, 77.9% of mortality, and 73.1% of unexpected morbidity findings. These procedure groups included laparotomy, vascular procedures, thoracotomy, debridement, lower and upper gastrointestinal procedures, amputation, and therapeutic procedures on muscles and upper and lower extremity bones. Most common non-operative interventions included X-ray, ultrasound, wound care, catheterization, and intubation. Conclusions: Forward surgical team training and performance improvement metrics should focus on optimizing commonly performed operative procedures and non-operative interventions. Operative procedures that were commonly performed, and those associated with higher rates of morbidity and mortality, can set surgical benchmarks and outline training and skillsets needed by forward surgical teams.